Cancer in sub-Saharan Africa: a Lancet Oncology Commission. Issue 6 (June 2022) - Ngwa, Wilfred; Addai, Beatrice W; Adewole, Isaac; Ainsworth, Victoria; Alaro, James; Alatise, Olusegun I; Ali, Zipporah; Anderson, Benjamin O; Anorlu, Rose; Avery, Stephen; Barango, Prebo; Bih, Noella; et al.
Summary: In sub-Saharan Africa (SSA), urgent action is needed to curb a growing crisis in cancer incidence and mortality. Without rapid interventions, data estimates show a major increase in cancer mortality from 520 348 in 2020 to about 1 million deaths per year by 2030. Here, we detail the state of cancer in SSA, recommend key actions on the basis of analysis, and highlight case studies and successful models that can be emulated, adapted, or improved across the region to reduce the growing cancer crises. Recommended actions begin with the need to develop or update national cancer control plans in each country. Plans must include childhood cancer plans, managing comorbidities such as HIV and malnutrition, a reliable and predictable supply of medication, and the provision of psychosocial, supportive, and palliative care. Plans should also engage traditional, complementary, and alternative medical practices employed by more than 80% of SSA populations and pathways to reduce missed diagnoses and late referrals. More substantial investment is needed in developing cancer registries and cancer diagnostics for core cancer tests. We show that investments in, and increased adoption of, some approaches used during the COVID-19 pandemic, such as hypofractionated radiotherapy and telehealth, can substantially increase access to cancer care in Africa, accelerate cancer prevention and control efforts, increase survival, and save billions of US dollars over the next decade. The involvement of African First Ladies in cancer prevention efforts represents one practical approach that should be amplified across SSA. Moreover, investments in workforce training are crucial to prevent millions of avoidable deaths by 2030. We present a framework that can be used to strategically plan cancer research enhancement in SSA, with investments in research that can produce a return on investment and help drive policy and effective collaborations. Expansion of universal health coverage to incorporate cancer into essential benefits packages is also vital. Implementation of the recommended actions in this Commission will be crucial for reducing the growing cancer crises in SSA and achieving political commitments to the UN Sustainable Development Goals to reduce premature mortality from non-communicable diseases by a third by 2030.